Analisis Kestabilan Lereng Berdasarkan Kekuatan Geser Massa Batuan Terhadap Perubahan Kandungan Air Pada Tambang Batubara Di Area Blok Menyango - Novandri Kusuma Wardana (Jurusan Teknik Pertambangan, Fakultas Teknik, Universitas Bangka Belitung, 2019)
Mining activities is commonly to work with the problem of stability of rock mass, then befordesaining mine’s slope should know rock shear strength parameters, such as cohesion (c) andinternal friction angle value ( . Beside those parameters, also needed to know the impact ofwater content to the rocks. The water content will effect rock’s shear strength, proof by the rockcondition which is ductile when it is dry and soft when it is wet. Based on test results was doneusing sandstone with laboratory scale of direct shear test were analyzed using mohr – coulomband patton criteria (1966). It is known that the cohesion (c) of sandstone decreased from 510,35kPa at natural condition down to 133,75 kPa at wet condition. The internal friction angle ( ) alsodecreased from 54,56° at natural condition down to 48,45° at wet condition. The reduction of theshear strength is caused by fragments and clay minerals characteristics which are so reactiveand very easy to absorb water so that the cohesion of the sandstone reduce the active normalstress so that working the shear stress required to cause the shear failure becomeweaker. From the results, it is also known that the shear surface roughness had a lot ofinfluence on the shear strength the normal stresses applied on the direct shear tests werevery low under 20% of UCS.